2002
DOI: 10.1111/j.1349-7006.2002.tb01287.x
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Human Uroplakin Ia in Urinary Bladder Transitional Cell Carcinoma

Abstract: Uroplakins (UPs) Ia, Ib, II, and III are tissue-specific and differentiation-dependent transmembrane proteins of the urothelium. We assessed the usefulness of human UP Ia as a histological marker by examining its expression in urinary bladder transitional cell carcinoma (TCC). A polyclonal antibody against human UP Ia was raised using a synthesized polypeptide. We applied our antibody to various organ tissues, including urothelium, and observed no crossreactivity. Analysis by RT-PCR of normal urothelium, TCC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…We could detect cancer cells in the peripheral blood of urothelial cancer patients by nested reverse transcription-PCR and suggested molecular staging for micrometastasis (22)(23)(24). We also produced anti-human uroplakin Ia antibody and showed its usefulness as a specific histologic marker because of its stable expression even in metastatic lesions (25 ). However, in spite of much effort we could not establish a diagnostic method using uroplakins in sera or urine from patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could detect cancer cells in the peripheral blood of urothelial cancer patients by nested reverse transcription-PCR and suggested molecular staging for micrometastasis (22)(23)(24). We also produced anti-human uroplakin Ia antibody and showed its usefulness as a specific histologic marker because of its stable expression even in metastatic lesions (25 ). However, in spite of much effort we could not establish a diagnostic method using uroplakins in sera or urine from patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we investigated the urothelium-specific proteins, uroplakins, and their clinical application (22)(23)(24)(25). We could detect cancer cells in the peripheral blood of urothelial cancer patients by nested reverse transcription-PCR and suggested molecular staging for micrometastasis (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining was performed by the conventional avidin-biotin-peroxidase complex method (VECTASTAIN Elite ABC kit; Vector Laboratories Inc.), as described previously (26). Anti-human PLK-1 mAb (Transduction Laboratories) with a 1:100 dilution was used as the primary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Informed consent was provided according to the World Medical Association Declaration of Helsinki. Clinical and pathological data were obtained by retrospective chart review, as previously described (26).…”
Section: Methodsmentioning
confidence: 99%
“…8,9 Also, we have demonstrated that UPII and UPIII are cross-linked to UPIa and UPIb, respectively, suggesting the existence of 2 types of heterodimers, consisting of UPIa/UPII and UPIb/UPIII. 10,11 As UPs have been shown to be markers of urothelial differentiation by several independent investigators, [12][13][14][15][16] their level of expression might be low in poorly differentiated tumors. Nevertheless, we have shown previously that UPs are decreased at the protein level in such tumors; however, evidence indicates that even very poorly differentiated urothelial cells continue to express UPs at the mRNA level.…”
mentioning
confidence: 99%